Analisis Dampak Limbah Mayarakat Terhadap Pencemaran Lingkungan Di Pasar Mmtc Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Elsa Mutiara Panggabean; Rihandi Marpaung; Sri Ayuni (Fakultas Teknik Universitas Cenderawasih, 2023)
In this journal, the impact of public waste on environmental pollution in the MMTC market will be discussed. In previous research, it was found that waste management that is not environmentally friendly can have a negative impact on environmental health and society. Garbage can cause contamination of air surfaces and air bodies used by humans, disrupt life in the air, and cause unpleasant odors. Apart from that, rubbish can also cause shallowing of the air, resulting in blockages that can cause flooding. Therefore, public awareness and education is needed about good and correct waste management to minimize the negative impact of waste on the environment and public health. Case studies can be conducted to analyze waste management practices in the MMTC market, the type and amount of waste produced, as well as the impact of waste on the environment and public health. This study can also provide suggestions for improving waste management practices in the MMTC market and increase public awareness about good and correct waste management.